BLUP and Stability Analysis of Multi-environment Trials in Bread Wheat (Triticum aestivum L.) Genotypes under High Rainfall Conditions of Ethiopia - Dabi, Alemu; Duga, Ruth; Sime, Berhanu; Alemu, Gadisa; Zewdu, Demeke; Geleta, Negash; Solomon, Tafesse; Delessa, Abebe; Zegaye, Habtemariam; Asnake, Dawit; et al. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from June, 2020 to December, 2022 at Bekoji, Chefe Donsa, Debre Markos, Enewari, Gonder, Holeta, Kofele, Kulumsa, Robe Arsi and Sinana in Ethiopia to identify stable and high-yielding wheat genotypes resistant to stem and yellow rust disease. The study evaluated the performance of bread wheat genotypes across 21 high land environments in Ethiopia. Agronomic and quality traits, including days to heading, maturity, plant height, grain yield, hectoliter weight, thousand kernel weight, and disease resistance (stem rust and yellow rust), were recorded for each genotype in all environments. The results showed that the genotypes EBW182767 and EBW192345 were the top-yielding and stable genotypes across the 21 environments. These genotypes not only yielded significantly more than the standard checks, Boru and Danda’a but also demonstrated strong resistance to yellow and stem rust. EBW182767 outperformed the standard check Boru and Danda’a in terms of yield by 30.5% and 58.1%, respectively. Similarly, the second genotype EBW192345 was also produced a 25.4% and 51.9% yield advantage over the standard check (Boru) and (Danda’a), respectively. Because of their great performance and disease resistance, EBW182767 (named “Melka”) and EBW192345 (named “Gutu”) were released as new commercial varieties in 2024. These varieties can be used to create even better wheat varieties in the future and are also suitable for large-scale wheat farming in highland areas of Ethiopia.